Dynamics of Insulin Signaling in the Black-Legged Tick, Ixodes scapularis - Sharma, Arvind; Pooraiiouby, Rana; Guzman, Blanca; Vu, Preston; Gulia-Nuss, Monika; Nuss, Andrew B. (Frontiers in Endocrinology, 2019)
Insulin-like peptides (ILPs) have been identified in several invertebrates, particularly insects, and work on these ILPs has revealed many roles including regulators of energy homeostasis, growth, development and lifespan to name a few. However, information on arthropod ILPs outside of insects is sparse. Studies of Ixodid tick ILPs are particularly scarce, despite their importance as vectors of infectious agents, most notably Lyme disease. The recent publication of the genome of the black-legged tick, Ixodes scapularis, has advanced opportunities to study this organism from a molecular standpoint, a resource sorely needed for an organism with challenging life history requirements for study in the laboratory, such as a long life cycle and obligate, prolonged, blood-feeding at each life stage. Through bioinformatics searches of the tick genome and other available I. scapularis databases, we identified 4 four putative ILP sequences. Full-length sequences of these ILP transcripts were confirmed, and quantitative RT-PCR was used to examine expression levels of these ILPs in different life stages and adult tissues. This work serves as an initial characterization of ILP expression in ticks and provides the foundation for further exploration of the roles of ILPs in these important arthropod vectors.